Analysis of the Shortness of Hemodialysis Claim Files at Cililin Hospital - Erix Gunawan; Nurul Huda Fauziah (International Journal of Psychology and Health Science, 2025)
Hemodialysis services are essential therapy for chronic kidney failure patients who require regular service continuity, so that the smooth flow of claims to BPJS Kesehatan is a determining factor in maintaining the quality and continuity of service. However, practice in the field still shows that there are obstacles in the form of incomplete documents, delays in submission, and data inconsistency with the INA-CBGs standard, which has an impact on delayed disbursement of claims and the potential for disruption of hospital financial stability. This study aims to analyze the completeness of the hemodialysis claim file management system at Cililin Hospital, focusing on the level of inter-unit integration, the effectiveness of procedures, and factors that affect claim approval. The research method uses a qualitative approach with a phenomenological design, involving the analysis of 80 claim files for the April 2025 period determined through the Slovin formula, as well as data collection through interviews, observations, and documentation studies. The results showed that the average level of claim completeness reached 86%, with the most complete patient identity component (90%) and the lowest completeness of medical records (81.25%). Of the total claims, 87.5% were approved and 12.5% were rejected, with the finding of a significant correlation between the completeness of the file and the level of claim approval. The conclusion of the study emphasized that the integration of hospital information systems, cross-unit coordination, and improving officer competence are the keys to the effectiveness of claims management. Theoretically, this study strengthens the information integration-based claims management literature, while practically providing improvement recommendations for regional hospitals to ensure the continuity of hemodialysis services and the financial sustainability of hospitals.